HIGHER ORDER THINKING SKILLS IN READING EXERCISES: A COURSE BOOK CONTENT ANALYSIS - Izzah, Naila Nurul; Adiarti, Dian; Kariadi, Mustasyfa Thabib (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2023)
Higher Order Thinking skills are greatly required by the students to have good critical thinking skills in response to the continuously developing globalization era with its challenges. This research aimed to analyze the distributions of questions found in open-ended reading exercises revealing whether or not the course book is sufficient to develop students’ critical thinking skills. This research used a qualitative method with content analysis to process the data found in open-ended reading exercises of English on Sky 3. Six cognitive levels (Remembering, Understanding, Applying Analyzing, Evaluating, and Creating) of the revised bloom's taxonomy theory were used to analyze each reading question and then classified into HOTS or LOTS. The results showed that 6 of 158 open-ended reading questions (3.80%) belonged to HOTS, while 152 of 158 reading questions (96.20%) belonged to LOTS. Analyzing (5 of 6 questions or 83.3%) was the most dominant cognitive level. Meanwhile, evaluating had only 1 of 6 questions (16.7%) and creating even had no distribution. In conclusion, the distribution of HOTS which was lower than LOTS, demonstrated that the open-ended reading exercises in English on Sky 3 were insufficient to develop students' critical thinking skills.